The Christ and the Spirit ; v. 1 collected essays - Dunn, James Douglas Grant, 1939- (Grand Rapids, MI Eerdmans, 1998)
Contents : v. 1 : Christology.
Keywords: Jesus Christ -- Person and offices -- Biblical teaching; Jesus Christ -- History of doctrines -- early church, ca. 30 - 600.; Holy Spirit -- History of doctrines -- early church, ca. 30 - 600.; Bible. N.T. -- theology; Holy Spirit -- Biblical teaching